조형원리를 기반으로 한 꽃의 조형요소에 관한 연구 -꽃의 구조에 따른 조형 분류를 중심으로 - 이미향; Lee¸ Mi Hyang; 김흥렬; Kim¸ Heung Ryeol (기초조형학연구, 2021)
꽃은 일상 및 예술을 비롯한 인류 문화의 모든 영역에서 미의 영감의 원천이 되어왔다. 화예디자인은 꽃과 식물의 생명력을 표현하는 조형예술 분야로 그 영역이 확장되고 있지만 객관적 미학의 대상으로 서 꽃의 심미성에 관한 탐구는 아직 미약하다. 따라서 꽃의 아름다움에 대한 체계적인 탐구는 꽃에 대 한 새로운 해석과 함께 미학의 또 다른 분야를 열어줄 것으로 기대된다. 본 연구는 꽃의 아름다움을 객관화하기 위해 정량적 방법으로 꽃의 조형요소를 체계화하는데 목적이 있다. 연구과정은 디자인에 서의 조형성 유형을 선행연구로, 식물학적 꽃부리 분류체계의 고찰을 통한 꽃의 분류체계 범위 내에서 꽃의 형상적 조형요소를 분석, 연구를 진행하였다. 그러나 식물학적 분류 체계에 따라 다소 범위의 차 이가 있는 것을 감안하여 관련 서적과 인터넷 자료를 토대로 6개의 분류 방식에서 도출된 총 114개의 꽃 가운데, 단 하나의 유형으로 분류되거나 기준이 다른 것을 제외한 103개를 분석 대상의 범위로 하였다. 연구결과 첫째, 꽃의 형태에 따른 조형적 꽃부리의 범위와 내용을 정리, 총 18개의 항목이 분류 되었으며 식물학 분류 체계에 없는 부분이 일부 추가되었다. 둘째, 꽃의 조형적 특징으로 대칭성이 두드러짐을 확인하였다. 셋째, 정면 모양에서 좌우대칭형과 함께 방사대칭형 중 오각형의 꽃이 다수 도출되었다. 넷째, 꽃의 색채에서는 명도대비가 주요한 특성으로 나타났다. 다섯째, 이를 기초로 꽃의 객 관적 분석 자료로 활용할 수 있는 꽃부리 형태와 색채 분석 모듈을 정리하였다. 본 연구는 꽃의 사례 범위가 제한적이기는 하지만 꽃의 조형적 특징을 정량적 요소로 분석함으로써 꽃의 아름다움의 객관 적 측정 가능성을 확인하였고, 연구에서 제시한 꽃부리의 조형요소 통합분석모듈은 차후 꽃의 사용목 적과 범위에 따라 꽃의 미적 요소에 대한 객관적 자료의 군집별 발췌 가능성이 예상되며, 나아가 본 연구의 결과가 꽃의 객관적 미학을 위한 후속 연구의 밑거름이 되기를 기대한다. Flowers have been a source of inspiration for beauty in all areas of human culture, including everyday life and arts. Flower Design is a field of formative arts with flowers as its medium, but regarding the subject of objective aesthetics, the research for its aesthetic beauty, are still weak. Thus, exploring the objectivity of the beauty of flowers is expected to open up an another chapter of its aesthetics with a new interpretation of flowers. This study aims to systematize the aesthetic principle of flowers in quantitative ways based on the flower’s figurative elements. The process of the research was developed with the botanical flower corolla classification system to analyze the shaping elements according to the shape of the flower, and conducted the scope of the classification of the flower accordingly. However, considering the differences in the scope of botanical classification, 103 flowers out of a total of 114 types derived from six different classifications based on related books and Internet data were included in the analysis, excluding those classified as a single type or with different criteria. First according to the results of the study, the scope and contents of the formative corolla from the shape of the flowers, were organized into 18 categories, and some of the missing parts of the botanical classification system have been added. Second, the symmetry of flowers, especially the radial symmetry with pentagonal flowers, and the lightness contrast were found to be prominent. Third, based on this, the formative corolla and color analysis module system was organized. Although the range of flower cases were limited, this study confirmed the possibility of an objective measurement for the beauty of flowers by analysing the flower’s formative characteristics as quantitative factors, and the integrated analysis module for the element forms of a corolla presented in the study is expected to be the basis for subsequent research on flower object aesthetics, depending on the purpose and field of the use of flowers in the future.